Climate change and the macro economy - Malin Andersson; Claudio Baccianti; Julian Morgan (European Central Bank (ECB), 2020)
This Occasional Paper reviews how climate change and policies to address it may affect the macro economy in ways that are relevant for central banks' monetary policy assessment of the inflation outlook. To this end, the paper focuses on the potential channels through which climate change and the policy and technological responses to climate change could have an impact on the real economy. Overall, the existing literature suggests a likelihood that climate change will have demand-side implications, but will also cause a negative supply shock in the decades to come and may even have the potential to lead to widespread disruption to the economic and financial system. We may already be observing a rise in the costs resulting from an increased incidence of extreme weather conditions. The direct effects stemming from climate change are likely to increase gradually over time as global temperatures increase. Nevertheless, it is extremely difficult to obtain reliable estimates of the overall macroeconomic impact of climate change, which will also depend on the extent to which it can be brought under control through mitigation policies requiring major structural changes to the economy. In order to implement such policies political economy obstacles will need to be overcome and measures will need to be put in place that address underlying market failures. They could involve significant fiscal implications, with an increased price of carbon contributing to higher overall prices. At the same time, these measures could also foster innovation, generate fiscal revenues and dampen inflationary pressures as energy efficiency increases and the price of renewable energy falls.
Keywords: Q43; Q54; Q55; Q58; 330; energy; macro economy; climate; global warming; technological innovation; government policy